2016
DOI: 10.1080/10580530.2016.1188545
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Resource Planning Systems Introduction and Internal Auditing Legitimacy: An Institutional Analysis

Abstract: In this paper, the authors examine how the internal audit function (IAF) maintains its legitimacy when enterprise resource planning (ERP) systems are introduced. This work centers on an in-depth case study of a multinational bank and finds that ERP systems impose an institutional logic of control based on interlinked assumptions. These assumptions motivate changes in the practice and structure of the IAF to become an integrated and comprehensive function to maintain its legitimacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…The ERP systems that employ continuous audit functions are the most essential factors in the effective application of fraud reduction approaches. Elbardan et al (2016), investigates how well the internal audit function (IAF) keeps its authenticity once ERP controls are installed. The results indicate that the auditors' best way to respond to the implementation of ERP systems changed to compliance for two reasons: first, internal auditors believed that adaptation was compatible with international auditing standards, and second, internal auditors participate in Implementation of ERP.…”
Section: Methodology and Literature Reviewsmentioning
confidence: 99%
“…The ERP systems that employ continuous audit functions are the most essential factors in the effective application of fraud reduction approaches. Elbardan et al (2016), investigates how well the internal audit function (IAF) keeps its authenticity once ERP controls are installed. The results indicate that the auditors' best way to respond to the implementation of ERP systems changed to compliance for two reasons: first, internal auditors believed that adaptation was compatible with international auditing standards, and second, internal auditors participate in Implementation of ERP.…”
Section: Methodology and Literature Reviewsmentioning
confidence: 99%
“…It should be noticed that very limited crosscountry studies (four articles) have been found, which could provide a comparison between different market policy implementations and cultural impact on different aspects of IA. For example, Elbardan and Ali (2011) studied the IAFs and the implementation of enterprise resource planning systems in the UK and Egypt. (2003) to assess the issues in the development of the IA in Saudi Arabia and found that IA is not well developed because of some restrictions on their degree of independence and a lack of qualified staff.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…An effective internal control system can properly regulate the company's various operations and contribute greatly to its sustainable and stable operation (Aziz et al 2017). The parent company may release subsidiary annual internal audit plans according to each subsidiary's business characteristics and business scale and assign auditors to supervise the plan's implementation (Elbardan et al 2016). The parent company should regularly review subsidiary financial reports to evaluate their performance and strengthen supervision of the auditing process.…”
Section: Integrated Audit Managementmentioning
confidence: 99%